2020
DOI: 10.1038/s41467-020-15163-6
|View full text |Cite|
|
Sign up to set email alerts
|

The Aurora B specificity switch is required to protect from non-disjunction at the metaphase/anaphase transition

Abstract: The Aurora B abscission checkpoint delays cytokinesis until resolution of DNA trapped in the cleavage furrow. This process involves PKCε phosphorylation of Aurora B S227. Assessing if this PKCε-Aurora B module provides a more widely exploited genome-protective control for the cell cycle, we show Aurora B phosphorylation at S227 by PKCε also occurs during mitosis. Expression of Aurora B S227A phenocopies inhibition of PKCε in by-passing the delay and resolution at anaphase entry that is associated with non-disj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Although CDK complexes such as Cyclin B-CDK1 phosphorylate a plethora of crucial M-phase substrates, containing minimal [S/T]P and full consensus [S/T]PXX[L/R] motifs [94][95][96][97], it is now clear that at least one CDK enzyme complex can also phosphorylate non-[S/T]P consensus motifs [98], operating through a combined 'multisite' code [99], differential substrate co-localisation and ordered phosphorylation that is dependent on substrate affinity [100,101]. Similar findings have also been made with the abscission-controlling PKCε-Aurora B complex, whose substrate specificity can switch at different phases of the cell cycle [102]. In the context of PLK4, further studies with full-length proteins are justified to examine whether PLK4 substrate specificity might be altered depending upon the subcellular repertoire of regulatory proteins/substrates formed.…”
Section: Discussionmentioning
confidence: 99%
“…Although CDK complexes such as Cyclin B-CDK1 phosphorylate a plethora of crucial M-phase substrates, containing minimal [S/T]P and full consensus [S/T]PXX[L/R] motifs [94][95][96][97], it is now clear that at least one CDK enzyme complex can also phosphorylate non-[S/T]P consensus motifs [98], operating through a combined 'multisite' code [99], differential substrate co-localisation and ordered phosphorylation that is dependent on substrate affinity [100,101]. Similar findings have also been made with the abscission-controlling PKCε-Aurora B complex, whose substrate specificity can switch at different phases of the cell cycle [102]. In the context of PLK4, further studies with full-length proteins are justified to examine whether PLK4 substrate specificity might be altered depending upon the subcellular repertoire of regulatory proteins/substrates formed.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). It has been shown that physiologically, caspase activation can also drive V3 domain cleavage ( Basu et al, 2002 ) and this turns out to be central to an M-Phase engagement of PKCε (see further below ( Kelly et al, 2020 )). A second non-canonical activation pathway for PKCε involves the assembly of a PKCε-14-3-3 complex ( Saurin et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently the mechanism of PKCε engagement in this process has been addressed and this is of particular interest given the chromatin-associated changes involved in the SAC silencing delay and the conventional activation of PKCε in membrane compartments (see above). Notably in the context of this compartmental issue, it has been reported that there is a constitutive cell cycle dependent activation of PKCε in a chromatin sub-compartment that is effected by V3 domain cleavage ( Kelly et al, 2020 ). Proteolysis occurs principally through Caspase 7 acting at Asp383 (the critical, activating V3 domain site) and Asp451 (kinase domain site), in line with earlier caspase site mapping work ( Basu et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations